Conductance relaxation in Langmuir-Blodgett manganese phthalocyanine (PcMn) films in inhomogeneous electrical field - Kazantseva, Z.; Kislyuk, V.; Kozyarevych, I.; Lozovski, V.; Tretyak, O. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2005)
The conductance relaxation of Langmuir-Blodgett films of manganese phthalocyanine in inhomogeneous electrical field was studied. Inhomogeneous electrical field was achieved by using the lateral surface of reverse-biased Si p-n junction. The conductance of new film increases up to saturation with the characteristic time about 10 hours. After that the film has been kept in air for a long time (about 50 days), on application of the back bias the conductance slowly decreased with the characteristic time more than 10 hours. These properties are associated with appearance or disappearance of the bonds between molecular stacks in the film.